Response of two Chickpea genotypes to different fertilizers composition and different application forms - Kamil Mohamed saleem; Kawa Abdulkareem Ali (Zanco Journal of Pure and Applied Sciences, 2021)
A field study was conducted at Grdarashe experimental field (Latitude: 36° 4’ N and Longitude: 44° 2’ E- elevation 415 m above Sea level), college of Agricultural engineering sciences, Salahaddin University, Erbil Iraqi Kurdistan Region, to investigate the effect of different fertilizers on growth and yield component of two Kabuli Chickpea (Cicer arietinum L.) genotypes, Sham and Mexican; the fertilizers composed of five treatments Bio- fertilizer, Foliar applied fertilizer, Urea as a source of nitrogen, di- ammonium phosphate (DAP), and No fertilizer as a control. The experiment designed in completely randomized block. The results showed a significant increase in plant height when treated with foliar fertilizer compared to the control treatment. Di-ammonium phosphate (DAP) treatment was recorded the largest number of primary and secondary branches per plant compared to control treatment. The Number of pods, seed.plant-1 and pods.plant-1, seeds weight (g.plant-1), 100 seeds weight (g) ,biological and economical yield(ton.ha-1),harvest index, protein and fiber ratio increased with Bio-fertilizer treatment, which recorded the highest value compared to the others treatments.